Analisis Etika Komunikasi Kepemimpinan Gampong (Desa) di Aceh - Muhammad Syarif (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2023)
This study focuses on the ethics of leaders in communicating with the public and the effectiveness of the ethics of communication with the community. Qualitative methodology with a descriptive approach to data collection techniques by observation and interviews. The results of the study show that the ethics of leaders in communicating with the community in a village built by leaders who lack ethics in communication so that it is clear that changes to the welfare of the community that occur without having to be assessed from another perspective. Because every human being has a feeling of wanting to be appreciated and wanting to appreciate. When the feeling of wanting to be respected is ignored, the sense of respect cannot be realized so that divisions occur within one community group. Seriousness can be seen based on research results. Not solely because of that, but the way of a good leadership is when the feedback received is in accordance with the expectations desired by a community which is a common goal. The effectiveness of the leader's communication ethics towards the community, that is, ineffective communication ethics will have an impact on social inequalities in society, a sense of togetherness and cooperation will no longer work effectively and will make an area of leadership immoral and dignified